Effects of intense running to exhaustion on the in-shoe plantar pressure patterns in young middle-distance athletes - Fourchet, F.; Kelly, L.; Horobeanu, C.; Millet, G. P. (ESM 2010 emed scientific meeting, 2010)
It has been reported that intense exhaustive running increased forefoot loading in experienced adult runners and may explain some foot/ankle overuse injuries (Weist 2004). However to ourknowledge no studies investigated that topic in adolescent athletes. The aim of this study was to examine the effects of intense running to exhaustion (Tlim) on the in-shoe plantar pressure patterns in young elite middle-distance athletes